Stroke network performance during the first COVID-19 pandemic stage: A meta-analysis based on stroke network models. Issue 7 (October 2021) - Romoli, Michele; Eusebi, Paolo; Forlivesi, Stefano; Gentile, Mauro; Giammello, Fabrizio; Piccolo, Laura; Giannandrea, David; Vidale, Simone; Longoni, Marco; Paolucci, Matteo; Hsiao, Jessica; Sayles, Emily; et al.
Background: The effect of the COVID pandemic on stroke network performance is unclear, particularly with consideration of drip&ship vs. mothership models. Aims: We systematically reviewed and meta-analyzed variations in stroke admissions, rate and timing of reperfusion treatments during the first wave COVID pandemic vs. the pre-pandemic timeframe depending on stroke network model adopted. Summary of findings: The systematic review followed registered protocol (PROSPERO-CRD42020211535), PRISMA and MOOSE guidelines. We searched MEDLINE, EMBASE, and CENTRAL until 9 October 2020 for studies reporting variations in ischemic stroke admissions, treatment rates, and timing in COVID (first wave) vs. control-period. Primary outcome was the weekly admission incidence rate ratio (IRR = admissions during COVID-period/admissions during control-period). Secondary outcomes were (i) changes in rate of reperfusion treatments and (ii) time metrics for pre- and in-hospital phase. Data were pooled using random-effects models, comparing mothership vs. drip&ship model. Overall, 29 studies were included in quantitative synthesis (n = 212, 960). COVID-period was associated with a significant reduction in stroke admission rates (IRR = 0.69, 95%CI = 0.61–0.79), with higher relative presentation of large vessel occlusion (risk ratio (RR) = 1.62, 95% confidence interval (CI) = 1.24–2.12). Proportions of patients treated with endovascular treatment increased (RR = 1.14, 95%CI = 1.02–1.28). Intravenous thrombolysis decreased overall (IRR = 0.72, 95%CI = 0.54–0.96) but not in the mothership model (IRR = 0.81, 95%CI = 0.43–1.52). Onset-to-door time was longer for the drip&ship in COVID-period compared to the control-period (+32 min, 95%CI = 0–64). Door-to-scan was longer in COVID-period (+5 min, 95%CI = 2–7). Door-to-needle and door-to-groin were similar in COVID-period and control-period. Conclusions: Despite a 35% drop in stroke admissions during the first pandemic wave, proportions of patients receiving reperfusion and time-metrics were not inferior to control-period. Mothership preserved the weekly rate of intravenous thrombolysis and the onset-to-door timing to pre-pandemic standards.